Tumoral Calcinosis at a Finger Metacarpophalangeal Joint - Waltenspül, Claudia; Spies, Christian Karl; Janzen, Jan (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
A 51-year-old patient presented with a painful swelling palmar to the metacarpophalangeal joint of the ring finger. A round tumor was detected using X-rays and MRI. After excision, tumoral calcinosis could be verified histologically.
Keywords: Morbus Teutschlaender; tumoral calcinosis; hand surgery